A Rare Cause of Splanic Vein Trombosis: Factor V Leiden Mutation Is - Dicle, K.; Ulusoy, A.N.; Çinar, H.; Demir, M.; Şeren, T.D.; Kesicioglu, T. (Samsun 55139, 2009)
Clotting is a process that occurs following the consecutive reactions of almost 20 different molecules in the blood. The diseases that appear due to the mutation of these molecules resulted in, intravascular thrombus bleeding. Our case who admitted to our hospital due to acute abdominal pain six year before was operated under the emergency conditions and superior mesenteric vein occlusion was observed. Partial resection of 70 cm small intestine with end to end anostomosis was performed. Faktör V leiden mutation was found in the postoperative diagnostic investigations Six year later, the same patient was admitted to our clinic with abdominal distention and diagnosed to be portal vein thrombosis and appropriate treatment was in this report, we presented the diagnostic and treatment characteristics of the case. © 2009 OMÜ Tüm Haklari Saklidir.
Nadir Splenik Ven Trombozu Sebebi: Faktör V Leiden Mutasyonu
Keywords: Anastomosis; Clotting Faktor; Early Diagnosis; Factor V Leiden Mutation; Surgical Treatment; Thrombus Constitution